PENGARUH GENDER TERHADAP KEINGINAN MAHASISWA AKUNTANSI DALAM MEMILIH PROFESI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK (Studi Kasus pada Mahasiswa Jurusan Akuntansi Fakultas Ekonomi Unisri Surakarta) - Edi Wibowo, Ernawati & (Universitas Slamet Riyadi, 2004)
ABSTRACT The study aims to know the significance of gender difference influence toward factors which affect the students of accounting department to choose the profession of public accountant and non public account. The study is conducted in faculty of economics UNISRI Surakarta with fifty respondents from the students of accounting department. To get sample, proportional simple random sampling is used, statistic test, and discriminate sample independent test is used to analyze the data. The result show that there is no significant difference between the factors affecting the students of accounting department to choose the difference among the factors which are considered to be able to differ the profession choice between public accountant and non public account. Variable order from the most important to less one in forming discriminate function are the variable of working opportunity for female respondent who choose public accountant and variable of working opportunity which is more important for those who choose non public accountant. For male responded working opportunity is more important variable for those who choose public accountant. Â Keywords: Gender, public accountant, students of accounting department